Faktor-faktor yang Memengaruhi Kejadian Bayi Berat Lahir Rendah di RS Sapta Medika Kecamatan Air Putih Kabupaten Batu Bara Provinsi Sumatera Utara Tahun 2024 - Sulistiawati Sulistiawati; Damayanty S; Anna Waris Nainggolan; Nuraisyah Nuraisyah; Ade Rachmat Yudiyanto (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Background​ Background LBW is still a concern for public health throughout the world and is associated with a number of short-term and long-term problems. More than 20 million births each year are estimated to be LBW, accounting for 15% to 20% of all births globally. In poor countries, the LBW birth rate is 16.5%, while in industrial countries it is 7%. Babies with low birth weight (LBW) may experience a number of problems and complications at birth. Metabolic problems, especially hypothermia, may appear in the short term. Method The research used is quantitative, information about what you want to know is examined using numerical data through a retrospective survey. Conducting a retrospective survey is one method of collecting historical data. This research uses a cross-sectional strategy. The sample for this in-depth research was all 60 mothers who gave birth at Sapta Medika Hospital. Analysis data using univariate and bivariate analysis. From the results of statistical tests it was found that p.value = 0.004 and α = 0.05, where the value of P.value (0.004) < α (0.05), so it can be concluded that there is a relationship between maternal age and the incidence of low birth weight (LBW) babies. ). Where the P value (0.019) < α (0.005), so it can be concluded that there is a relationship between maternal parity and the incidence of low birth weight (LBW) babies. Where the P.value (0.001) < α (0.05), so it can be concluded that there is a relationship between maternal nutritional status and the incidence of low birth weight (LBW) babies.